2022
DOI: 10.1186/s12915-022-01458-1
|View full text |Cite
|
Sign up to set email alerts
|

A bacteria-regulated gut peptide determines host dependence on specific bacteria to support host juvenile development and survival

Abstract: Background Commensal microorganisms have a significant impact on the physiology of host animals, including Drosophila. Lactobacillus and Acetobacter, the two most common commensal bacteria in Drosophila, stimulate fly development and growth, but the mechanisms underlying their functional interactions remain elusive. Results We found that imaginal morphogenesis protein-Late 2 (Imp-L2), a Drosophila homolog of insulin-like growth factor binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Similarly, development of this fruit fly is also symbiont dependent. The expression of imaginal morphogenesis protein-Late 2 (Imp-L2), depends on bacteriocyte harboring Acetobacter and Lactobacilli ( Lee et al, 2022 ). Studies have shown that the symbionts harboring the gut can activate gut nerves to send signals to brain nerves ( Forsythe and Kunze, 2013 ).…”
Section: Symbiotic Microbes: a Boon For Insectsmentioning
confidence: 99%
“…Similarly, development of this fruit fly is also symbiont dependent. The expression of imaginal morphogenesis protein-Late 2 (Imp-L2), depends on bacteriocyte harboring Acetobacter and Lactobacilli ( Lee et al, 2022 ). Studies have shown that the symbionts harboring the gut can activate gut nerves to send signals to brain nerves ( Forsythe and Kunze, 2013 ).…”
Section: Symbiotic Microbes: a Boon For Insectsmentioning
confidence: 99%
“…It was found that the expression of LMW PBP (Accession: F9UN64) in L. plantarum 67 was significantly downregulated in the N/C group (p < 0.05; Table 2) while being significantly upregulated in the P/N group (p < 0.05; Table 2). Therefore, upregulating the expression of related proteins in the peptidoglycan pathway by the PAs can improve the adhesion of L. plantarum 67 [50].…”
Section: Some Kegg Pathways Enrichment Analysismentioning
confidence: 99%
“…It is known that certain bacterial species from the Lactobacillus and Acetobacter genera promote fly larval development and growth especially upon undernutrition. In a GF condition, an undernourished fly larva shows stunted body growth and delayed development, which could be rescued by mono-association with specific commensal bacterial species, such as Lactobacillus plantarum (Lp) and Acetobacter pomorum (Ap) ( Erkosar et al, 2015 ; Lee et al, 2022 ; Matos et al, 2017 ; Shin et al, 2011 ; Storelli et al, 2011 ). L. plantarum exerts its beneficial effect on larval development through the host nutrient-sensing system, which depends on TORC1 activity in the adipose organ of the Drosophila and, subsequently, modulates the hormones regulating growth and maturation ( Storelli et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%